Resenha: CLAUDIO, Mario. Boa noite, senhor Soares. Rio de Janeiro: Sete Letras, 2009. 99 p. (Revista do Centro de Estudos Portugueses, 2010)
Resenha: CLAUDIO, Mario. Boa noite, senhor Soares. Rio de Janeiro: Sete Letras, 2009. 99 p.